Regulatory Lessons from Argentina's Power Concessions - Estache, Antonio (World Bank, Washington, DC, 2012)
In the early 1990s, Argentina vertically separated and privatized most of its electricity industry. Transmission and distribution, considered natural monopolies, were sold by concession. The main objectives of the reforms were efficient pricing and production levels in the short term and enough investment to meet demand over the longer term. The authors look at the design of the regulatory features of the concession contracts and discuss the implications for long-term investment in the power sector.